PEMBELAJARAN KITAB SAFINATUN NAJAH DALAM MEMBENTUK KARAKTER RELIGIUS SANTRI DI PONDOK PESANTRENAL-MUNAWWIR SANGATTA - Mega Ayu Utamima; Faelasup Faelasup (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The purpose of this research is to find out how the students at Al-munawwir Islamic Boarding School, located in Sangatta Selatan, are affected by studying the book Safinatun Najah. This research approach uses a qualitative descriptive method. Purposeful sampling will be used to select research participants, and observation, interviews, and documentation will be used to collect data. Reducing and summarizing data, presenting findings, and drawing conclusions are part of the data analysis process. Visualization and summary of data. Using data triangulation and source triangulation to confirm the truth of the information collected. Religious affiliation among santri is supported by the results of this study. Praying in congregation and reading wirid afterwards is a clear result of this study. the study of salaf books and reading the Qur'an, the entire religious circuit is carried out in accordance with Islamic principles.